2011
DOI: 10.2337/db10-1288
|View full text |Cite
|
Sign up to set email alerts
|

Drosophila Insulin Pathway Mutants Affect Visual Physiology and Brain Function Besides Growth, Lipid, and Carbohydrate Metabolism

Abstract: OBJECTIVEType 2 diabetes is the most common form of diabetes worldwide. Some of its complications, such as retinopathy and neuropathy, are long-term and protracted, with an unclear etiology. Given this problem, genetic model systems, such as in flies where type 2 diabetes can be modeled and studied, offer distinct advantages.RESEARCH DESIGN AND METHODSWe used individual flies in experiments: control and mutant individuals with partial loss-of-function insulin pathway genes. We measured wing size and tested bod… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
45
0
2

Year Published

2012
2012
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(52 citation statements)
references
References 23 publications
5
45
0
2
Order By: Relevance
“…Given that both proximal and distal components of insulin signaling-PI3K and InR respectively-are altered when JAK/STAT pathway is activated, convergence of the two pathways could occur at the direct downstream of InR activity or InR transcription level. It will be intriguing to uncover the exact confluence between the two pathways despite the dichotomy that exists between them: while insulin signaling is growth and proliferation-biased, JAK/STAT is immunological (71)(72)(73)(74). More so, this may provide insights into how immunity and metabolism differentially interact in normal development and pathologies.…”
Section: Discussionmentioning
confidence: 99%
“…Given that both proximal and distal components of insulin signaling-PI3K and InR respectively-are altered when JAK/STAT pathway is activated, convergence of the two pathways could occur at the direct downstream of InR activity or InR transcription level. It will be intriguing to uncover the exact confluence between the two pathways despite the dichotomy that exists between them: while insulin signaling is growth and proliferation-biased, JAK/STAT is immunological (71)(72)(73)(74). More so, this may provide insights into how immunity and metabolism differentially interact in normal development and pathologies.…”
Section: Discussionmentioning
confidence: 99%
“…Disruption of the insulin signaling pathway has a profound effect on Drosophila body size. Ablation of the IPCs (Rulifson et al, 2002), genetic deletion of Dilps (Grönke et al, 2010), or mutation of targets downstream of InR (Böhni et al, 1999;Brogiolo et al, 2001;Murillo-Maldonado et al, 2011) all result in a dramatic reduction in body size. However, despite the importance of the insulin signaling pathway for systemic growth in flies and for disease in humans, the factors regulating insulin secretion remain largely unknown.…”
Section: Introductionmentioning
confidence: 99%
“…In this regard, fly mutant growth phenotypes are similar to IRS1 loss-of-function mice models [30,31] and other murine diabetic models [32] where growth phenotypes also exist; besides, in flies, the insulin and IGF (insulin growth factor) pathways are mediated by a common route. In addition, fly mutants also have nervous system abnormalities [29].…”
Section: The Insulin Pathwaymentioning
confidence: 99%
“…Perhaps the clearest demonstration of the insulin pathway's role in carbohydrate and lipid metabolism comes from studies of Drosophila insulin pathway mutants: From the pioneering studies on Chico, a Drosophila insulin-receptor-substrate (IRS) homolog [10], it has now been demonstrated that practically all viable mutant combinations, that create partial loss-of-function or hypomorphic conditions for the insulin pathway, course with altered lipid and carbohydrate levels [29]. This is also akin to having congenital diabetes mellitus type 2, as these flies are born with a dysfunctional insulin pathway.…”
Section: The Insulin Pathwaymentioning
confidence: 99%